Semantic Encoding in Mild Cognitive Impairment: A Preliminary ERP Study - Kuo, Michael (International Clinical Neuroscience Journal, 2017)
Background: This study examines semantic encoding in mild cognitive impairment (MCI) using the event-related potential (ERP) technique. Subsequent memory effect (SME) is used as an index of successful memory encoding. Typically, SMEs are positive at P550 and late positive component (LPC) time windows. Methods: Ten MCI participants were recruited to complete the ERP experiment. A study and recognition paradigm was employed. Participants determined whether the item referred to by the Chinese character was able to produce sound at study phase and whether the Chinese character was studied at recognition phase while having their electroencephalograms recorded. Results: Behaviourally, correct percentage at study was 81% and reaction time was 998.5±325.5. Correct percentage at recognition was 61% (d prime=0.87±0.7). Significant SMEs were not identified in P550 and LPC windows. Conclusion: The behavioural and ERP results showed extensive cerebral deficits in MCI when performing semantic encoding. These deficits may be associated with assessing semantic memory and binding new information with long-term memory store.